2009
DOI: 10.1097/jto.0b013e31819852d5
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Hypoxia-Inducible Factor-1α mRNA and its Clinical Significance in Non-small Cell Lung Cancer

Abstract: The expression of HIF-1alpha mRNA is associated with disease progression in NSCLC tissues, and is expected as a biomarker or therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 44 publications
(31 reference statements)
3
23
0
Order By: Relevance
“…Nevertheless, a number of groups reported the correlation between increased mRNA and increased protein expression of Hif1α that also correlated to increased vascular density. Hif1α increased levels also correlated to increased VEGF levels that, as mentioned earlier, correlate to increased vascular density (43)(44)(45)(46)(47)(48)(49)(50)(51). We also show this pattern in our gene expression research which correlates to the increased vascular density, as observed in the grafts.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, a number of groups reported the correlation between increased mRNA and increased protein expression of Hif1α that also correlated to increased vascular density. Hif1α increased levels also correlated to increased VEGF levels that, as mentioned earlier, correlate to increased vascular density (43)(44)(45)(46)(47)(48)(49)(50)(51). We also show this pattern in our gene expression research which correlates to the increased vascular density, as observed in the grafts.…”
Section: Discussionsupporting
confidence: 87%
“…57,58 However, a large proportion of human tumors exhibit VEGF-A expression in the absence of HIF-1␣. 39 Although the VEGF-A promoter contains a HIF-1␣ binding site, 58 our study demonstrated negligible HIF-1␣ expression in lung cancer cells cultivated under ordinary conditions, and luciferase reporter assays revealed no significant association between the HIF-1␣ binding site and VEGF-A promoter activity. However, we also demonstrated here that HIF-1␣ was induced in lung cancer cells cultivated under hypoxic conditions and that EGR-1 expression enhanced HIF-1␣-induced VEGF-A expression.…”
Section: Discussionmentioning
confidence: 99%
“…Both HIF-1α and HIF-2α are frequently expressed in NSCLC, also during early progression of disease; but whereas HIF-2α causes, or is a surrogate marker for poor clinical prognosis (Giatromanolaki et al 2001), the role of HIF-1α in predicting outcome is debated. Some reports demonstrate that HIF-1α expression has no impact on patient overall survival (Giatromanolaki et al 2001;Kim et al 2005), but potentially contradictory data exist (Volm and Koomagi 2000;Yohena et al 2009). …”
Section: Non-small Cell Lung Carcinoma Hif Protein Expression Is Virmentioning
confidence: 99%